Stress of misfit dislocation at Fe/MgO interface drives the annihilation of radiation induced defects. (15th May 2021) - Du, J.L.; Chen, H.Q.; Xu, C.; Fan, Y.; Qiu, Y.H.; Wang, H.; Fu, E.G.
Abstract: Interfaces have the unique ability to trap and recombine Frenkel pairs generated during irradiation collision cascades. Better understanding of the mechanisms of interface sinking irradiation induced defects brings elaborate design of high irradiation tolerance materials through interface engineering. In this work, the mechanism of interface trapping and recombining irradiation induced defects was studied by using in situ irradiation experiments. The annihilation of irradiation induced defect clusters (DCs) was observed. The stress field of Fe/MgO interface with misfit dislocation array (MDA) was calculated and its effect on irradiation induced DCs was discussed. Combining the experimental and calculation, the factors to determine the sink efficiency of an interface to irradiation induced defects were investigated. Graphical abstract: Image, graphical abstract